PENYIDIKAN TINDAK PIDANA PENGANIAYAAN YANG MENYEBABKAN LUKA DI WILAYAH HUKUM KEPOLISIAN SEKTOR MANDAU - Nurmala, Sari; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The probe is to be discussed is the author of the investigation of criminal persecution that causes sores, which consists of minor injuries and severe injuries. Persecution is an act committed intentionally that causes an uneasy feeling, pain, or injury to another person's body. In the jurisdiction of Police Sector Saber persecution crime very rife, it is apparent in the level of complaints in the annual report. The purpose of this thesis, namely: first, to know the process of investigation of criminal persecution that causes sores in the Police Sector Saber, both to determine the causes of the slow process of investigation of criminal persecution that causes sores in the Police Sector Saber, third to find out the settings right of refusal Member Indonesian National Police in the case of criminal acts of persecution that causes sores in the Police Sector Saber.This type of research can be classified in this type of sociological research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in the District Saber Bengkalis Riau Province, while the sample population is a whole party with regard to the issues examined in this study, the data source used primary data and secondary data, data collection techniques in this study with interviews, questionnaires and the study of literature.From the research, there are three main things that can be inferred. First, the process of investigation of criminal persecution that cause injuries have not been implemented optimally and proven by many cases are not resolved in accordance with applicable law. Second, the causes of the slow process of investigation of criminal persecution that causes sores that police officers do not pay attention and did not complete a good job in carrying out its responsibilities, and their law enforcement officers handling the case to generate a conflict of interest. Third, setting right of refusal Members of the Indonesian Police were violated by the police. Advice writer, first, the police must continue to improve its performance in dealing with any cases. Second, improving the quality of police personnel should be done with the best. Third, members of the police should pay more attention and carry out their duties and obligations in accordance with the Code of Professional Ethics of the Indonesian Police and the Disciplinary Code Members of the Indonesian Police in solving criminal cases of persecution that causes sores in the district of Saber.Keywords: Investigation - Crime - Persecution - Injury